2017
DOI: 10.1123/jpah.2016-0466
|View full text |Cite
|
Sign up to set email alerts
|

Parental Physical Activity Associates With Offspring’s Physical Activity Until Middle Age: A 30-Year Study

Abstract: This study suggests that parents' physical activity assessed in their offspring's childhood contributes favorably to offspring's physical activity from childhood to middle age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 56 publications
3
26
0
3
Order By: Relevance
“…Adult obesity has experienced an alarming rise in the region, therefore this study differs from the mainstream studies in the age group of the sample that was investigated. The basis of choosing this age group is the claim that the environmental influence of parents differs between childhood and adulthood obesity [15]. While the majority of the parenting variables that we investigated have been substantiated in earlier studies, the principle findings of this study are as follows: The two novel parenting variables that are culturally unique to this region, i.e., the mother's age at childbirth and consanguineous marriage, showed significant differences between the two studied groups.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Adult obesity has experienced an alarming rise in the region, therefore this study differs from the mainstream studies in the age group of the sample that was investigated. The basis of choosing this age group is the claim that the environmental influence of parents differs between childhood and adulthood obesity [15]. While the majority of the parenting variables that we investigated have been substantiated in earlier studies, the principle findings of this study are as follows: The two novel parenting variables that are culturally unique to this region, i.e., the mother's age at childbirth and consanguineous marriage, showed significant differences between the two studied groups.…”
Section: Discussionmentioning
confidence: 63%
“…Globally, studies have focused to find the association of parental PA and ST in relation to the age of adolescence, since the maximum influence of parents has been found to occur during adolescence [14]. A recent long term longitudinal study (30 years), however, has found that parental PA is associated with increased levels of children's physical activity till the age of 24 years, which tends to remain until their midlife, thus making the age category of young adults (18 to 35 years) very significant in tackling adult obesity [15]. In the KSA, it is at this age when most of the people in the region get married and take independent decisions regarding the welfare of their respective families.…”
Section: Introductionmentioning
confidence: 99%
“…According to a tracking study of physical activity, an active lifestyle adopted early in childhood remains stable from youth to adult age [37]. In addition, parents' high levels of physical activity are positively associated with their children's activity levels [38]. According to Kaseva et al [38], the beneficial effect on offspring's lifestyle continues to at least middle age.…”
Section: Food-upbringingmentioning
confidence: 99%
“…In addition, parents' high levels of physical activity are positively associated with their children's activity levels [38]. According to Kaseva et al [38], the beneficial effect on offspring's lifestyle continues to at least middle age. The present study highlights the centrality of continuous activity in successful weight management.…”
Section: Food-upbringingmentioning
confidence: 99%
“…A focus on parent-child dyad analysis in preschool and preadolescent children is key to understanding the factors that are essential for shaping the active lifestyle of children, which persists until adulthood [ 11 , 12 ]. Numerous longitudinal studies confirm the persistence of obesity arising in preschool age to adolescence [ 13 , 14 ] and adulthood [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%